(untitled) (VERUM: Journal of Scientific Initiation, 2023)
This research primarily focuses on studying judicialization and its relationship/contribution to democracy. Since the study of this topic is quite diverse, the investigation is organized around two guiding axes: the substantive explanatory axis, which will be explored from the perspective of two important authors representing this approach, namely Ronald Dworkin and Mauro Cappelletti; and the procedural analytical axis, which will be examined in this theoretical essay through the perspectives of authors Antoine Garapon and Jürgen Habermas. Therefore, the general objective of this theoretical essay is to study the phenomenon of judicialization from the substantive explanatory and procedural analytical perspectives. The research problem is centered on questioning whether judicialization is a phenomenon of contemporary democracies. The methodology is deductive and uses bibliographic research of a qualitative nature, developed through the search for national publications in electronic databases such as Google Scholar and Scielo, as well as books and journals that focus on the study of the proposed theme.